2018
DOI: 10.3389/fphys.2018.01242
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Therapy Worsens Cardiac Function and Remodeling and Reverses the Effects of Exercise Training After Myocardial Infarction in Ovariectomized Female Rats

Abstract: There is an increase in the incidence of cardiovascular events such as myocardial infarction (MI) after menopause. However, the use of estrogen therapy (E2) remains controversial. The aim of this study was to evaluate the effects of E2, alone and combined with exercise training (ET), on cardiac function and remodeling in ovariectomized (OVX) rats after MI. Wistar female rats underwent ovariectomy, followed by MI induction were separated into five groups: S; MI; MI+ET; MI+E2; and MI+ET+E2. Fifteen days after MI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 64 publications
0
8
0
3
Order By: Relevance
“…Kauser et al [170] first found that there were gender differences in the production and release of NO, and the release of NO in the aorta of female rats was higher than that of males. Estrogen maintains the bioavailability of NO by increasing the expression of eNOS mRNA and protein, thus increasing the production of NO in endothelial cells and vascular smooth [167,[184][185][186][187][188][189][190] Estrogen restored antioxidant enzymes GPX1 and GPX4 expression levels Oxidative stress balance was maintained [158,181,189] Estrogen increased the expression of the glutathione rate-limiting enzyme γ-glutamylcysteine synthetase Oxidative stress balance was maintained [168,190,191] Estrogen maintained the bioavailability of NO by increasing the expression of eNOS mRNA and protein…”
Section: Estrogen Inhibits Oxidative Stressmentioning
confidence: 99%
“…Kauser et al [170] first found that there were gender differences in the production and release of NO, and the release of NO in the aorta of female rats was higher than that of males. Estrogen maintains the bioavailability of NO by increasing the expression of eNOS mRNA and protein, thus increasing the production of NO in endothelial cells and vascular smooth [167,[184][185][186][187][188][189][190] Estrogen restored antioxidant enzymes GPX1 and GPX4 expression levels Oxidative stress balance was maintained [158,181,189] Estrogen increased the expression of the glutathione rate-limiting enzyme γ-glutamylcysteine synthetase Oxidative stress balance was maintained [168,190,191] Estrogen maintained the bioavailability of NO by increasing the expression of eNOS mRNA and protein…”
Section: Estrogen Inhibits Oxidative Stressmentioning
confidence: 99%
“…Whereas short-term administration of E2 after MI would seem harmful, as it increases infarction area in OVX-MI rats, long-term treatment with E2 normalizes ventricular wall tension and chamber dimension in these animals by regulating the endothelin system and promoting increased survival [ 41 ]. Recent work has demonstrated that long-term E2 administration to OVX-MI rats failed to prevent cardiac dysfunction and remodeling [ 67 ]. Interestingly, OVX rats subjected to ischemia-reperfusion (I/R) present significantly decreased post-ischemic recovery of left ventricular function and increased MI extension, and these deleterious effects were avoided by E2 [ 68 ].…”
Section: Er Modulation and Mi: Preclinical Studiesmentioning
confidence: 99%
“…8,10,33 Apenas alguns pesquisadores analisaram os efeitos do exercício no coração de ratos com IM pequeno. 35,36 Ao iniciarem o exercício dentro de quatro semanas após a indução do IM, esses autores observaram efeitos benéficos do exercício físico. 35,36 Neste estudo, mostramos pela primeira vez que o exercício aeróbico tardio, iniciado três meses após o IM, quando a remodelação cardíaca está estável, atenua as alterações da geometria cardíaca em ratos com pequeno infarto.…”
Section: Discussionunclassified
“…35,36 Ao iniciarem o exercício dentro de quatro semanas após a indução do IM, esses autores observaram efeitos benéficos do exercício físico. 35,36 Neste estudo, mostramos pela primeira vez que o exercício aeróbico tardio, iniciado três meses após o IM, quando a remodelação cardíaca está estável, atenua as alterações da geometria cardíaca em ratos com pequeno infarto. Nosso estudo, portanto, reforça o conceito de benefício potencial da reabilitação cardíaca após síndromes coronarianas agudas, independentemente do grau de lesão cardíaca.…”
Section: Discussionunclassified